Investigating mentor commitment in youth mentoring relationships: The role of perceived program practices. Issue 7 (11th July 2020) - Drew, Alison L.; Keller, Thomas E.; Spencer, Renée; Herrera, Carla
Abstract: Highly committed mentors may be less likely to end their mentoring relationships with their mentees. Theory suggests commitment is predicted by relationship satisfaction, investment, and perceptions of available alternatives. Mentoring program practices may influence commitment, but little research has investigated potential mechanisms. Using data from 537 mentors representing 55 mentoring programs, this study examined a theoretical path model in which mentor perceptions of program practices, specifically setting expectations, prematch mentor training, and matching based on mentor preferences, predict mentor satisfaction, investment, perceptions of available alternatives, and ultimately, relationship commitment. As expected, commitment was associated positively with satisfaction and investment and negatively with available alternatives. Perceptions of the program setting clear expectations, the amount of prematch training, and matching by preferences predicted mentor commitment. These associations were mediated by relationship satisfaction, investment, and available alternatives, respectively. These findings identify program practices that can support mentor commitment.